Anxiety and Depression among Patients with Chronic Obstructive Pulmonary Diseases in Pulmonology Unit of Nobel Medical College Teaching Hospital - Jha, Nilam Kumari; Jha, Komal Kant (Birat Journal of Health Sciences, 2021)
Introduction: Anxiety and Depression is a common comorbidity in chronic obstructive pulmonary disease patients. Impaired lung function is a risk factor for depression In COPD patients, reduced recreational activities and social Isolation is a major risk factor resulting in anxiety and depression. Objective: The objective of this study is to evaluate the prevalence of Anxiety and Depression among the COPD patients at Pulmonology unit of Nobel Medical College Teaching Hospital. Methodology: A hospital based cross- sectional research design was used for the study. A total of 185 patients with previously diagnosed COPD. Data were collected by using a face to face interview technique in patients to evaluate anxiety and depression using Nepali version of Hospital Anxiety and Depression Scale questionnaire at Nobel Medical College Teaching Hospital, Biratnagar, Nepal from May to August 2020. Data analysis were done by descriptive and inferential statistics. Results: A total of 185 patients participated in the study, 157 patients (84.9%) had anxiety, 107 patients (57.8%) had depression and 102 patients (55.1%) had both anxiety and depression. There was statistically significant association of anxiety and depression in COPD patients with age, religion, occupation, smoking status, duration of illness, history of previous hospitalization, number of hospitalization in previous year, type of family, domiciliary oxygen therapy. Conclusion: The study concluded that anxiety and depression had been most prevalent in COPD patients. Therefore health personnel working in the Pulmonology unit should be aware the early assessment and treatment of anxiety and depression of chronic obstructive pulmonary diseases patients.